Innovation and Sustainable Development in Refugee Camps: Concrete Action: Twin-pit VIP latrine and large ferro-cement water tank - Kreuzer, Fabian Maximilian (Consilience, 2010)
This paper researches the possibility to increase sustainable development in long-term protracted refugee situations and the work of UNHCR in applying technological innovations. As a case study, examples from the lessons learned in the Nepalese camps are given. The paper therefore refers to the comprehension of sustainable development by the Brundtland commission (NOT the meaning of durable solutions in UNHCR-terms). The areas of research are sanitation and water supply / storage where two innovations are examined, the twin-pit VIP latrine and the large ferro-cement water tank. In sum the researched innovations contributed through: Economizing scarce (donor) resources as twin-pit VIP latrines may decrease costs up to ¼ of alternative options and ferro-cement water tanks can be constructed with low cost local material whereas plastic tanks need to be imported. Improving social quality in the camps through lavatory facilities to be constructed for each family rather than a community to decrease sexual violence and increase dignity as well as water tanks involving the community in construction and maintenance thus providing employment rather than providing pre-constructed ones. Facilitating environmental protection as 1/10 less land is occupied with decomposition of latrine waste and ferro-cement water tanks can be used up to three times longer than other models. Therefore, a checklist for the field is proposed to recall at all times the importance of innovations for sustainable development. Dimension of sustainable development Innovation in sanitation available? Innovation in water supply chain available? Economical YES/NO YES/NO Social YES/NO YES/NO Environmental YES/NO YES/NO Thus, the article intends to encourage scholars to make use of its findings and checklist in other areas with the same conditions. Findings may therefore be relevant for urban planning in slums and other extreme situations with heavy limited resources, but also engineers and other technical innovators who should consider the impact of their work concerning sustainable development.